Pancreatic Hydatid Cyst Misdiagnosed as Mucinous Cystadenoma: CT and MRI Findings - Milica Mitrovic; Boris Tadic; Jelena Kovac; Nikola Grubor; Vladimir Milosavljevic; Aleksandra Jankovic; Igor Khatkov; Dejan Radenkovic; Slavko Matic (Medicina, 2020)
Isolated hydatid cysts of the pancreas are rare lesions, even in endemic regions. In this report, we present the case of a 76-year-old patient who was admitted to our clinic with a diagnosis of a cystic lesion in the tail of the pancreas. On preoperative computed tomography (CT) and magnetic resonance (MR) examination, the cyst was characterized as a mucinous cystadenoma. A laparoscopic distal pancreatectomy followed. A histopathological examination revealed a large hydatid cyst in the tail of the pancreas.